2014
DOI: 10.1021/jo500714b
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Structure of an N-Terminal β-Turn To Maximize Screw-Sense Preference in Achiral Helical Peptide Chains

Abstract: Oligomers of α-aminoisobutyric acid (Aib) are achiral peptides that typically adopt 3 10 helical conformations in which enantiomeric left-and right-handed conformers are, necessarily, equally populated. Incorporating a single protected chiral residue at the N-terminus of the peptide leads to induction of a screw-sense preference in the helical chain, which may be quantified (in the form of "helical excess") by NMR spectroscopy. Variation of this residue and its N-terminal protecting group leads to the conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
112
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(119 citation statements)
references
References 163 publications
6
112
1
Order By: Relevance
“…19 In solution, these "foldamers" 20 populate almost exclusively 21 two rapidly exchanging conformational states of left or right handed helical screw sense, with the relative population of these two states being remarkably sensitive to chiral influences. [22][23][24][25] A chiral ligand covalently 15 or non-covalently 16 bound to one terminus of an Aib foldamer will propagate its conformational influence through the entire foldamer length. 26 In this way endto-end transmission of binding information over multi-nanometre distances has been accomplished through Aib foldamers dissolved in organic solvents.…”
mentioning
confidence: 99%
“…19 In solution, these "foldamers" 20 populate almost exclusively 21 two rapidly exchanging conformational states of left or right handed helical screw sense, with the relative population of these two states being remarkably sensitive to chiral influences. [22][23][24][25] A chiral ligand covalently 15 or non-covalently 16 bound to one terminus of an Aib foldamer will propagate its conformational influence through the entire foldamer length. 26 In this way endto-end transmission of binding information over multi-nanometre distances has been accomplished through Aib foldamers dissolved in organic solvents.…”
mentioning
confidence: 99%
“…48b Changing the solvent from THF-d8 to CD3CN decreased the value of Δδ at all ratios of proton sponge:1a. Comparison with known values for Δδ in these solvents 51 suggested that while 2a induced a screw sense preference in 1a of 28% helical excess (h.e.) in solution in THF-d8, the induction of screw sense preference in CD3CN reaches only 16% h.e.…”
Section: Introductionmentioning
confidence: 95%
“…48, 49 We now report the intramolecular, non-covalent induction of a conformational preference in an amide foldamer purely through hydrogen-bonded interactions between a chiral anion and a suitable geometrically matched binding site incorporating a urea function. Four foldamers, 1a-d (Fig 1) were synthesised, in each of which an achiral but helical Aib pentamer 50,51 is capped, at its N-terminus, by a urea function. At the C-terminus, the terminal Aib carries a pair of 13 C-labelled methyl groups to act as a marker of conformational induction.…”
Section: Introductionmentioning
confidence: 99%
“…The two screw‐sense conformers of an Aib oligomer may be desymmetrised by ligation to a chiral terminus,23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33 which leads to an imbalance in the population of the two interconverting screw‐sense conformers 34,35. This imbalance may be quantified by NMR,27 and a C terminal AlaNHR residue, for example, may induce a 99:1 preference for right‐handed screw sense in an attached Aib oligomer chain 25.…”
mentioning
confidence: 99%